MANAJEMEN BIROKRASI DALAM PENGEMBANGAN KARIR DAN PROMISI JABATAN DI DINAS KESEHATAN KABUPATEN POLEWALI MANDAR - Abd Khalik; Muhammad Awarih (MITZAL (Demokrasi, Komunikasi dan Budaya) : Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2020)
This study aims to describe and analyze the influence of career development and promotion at the Polewali Mandar District Health office. Data collection techniques through observation, interviews, and image documentation. The results showed that career development as the empowerment of ASN in the Polewali Mandar Health Service was in accordance with Law Number 5 of 2014 concerning ASN. Employees pay attention to discipline, education levels and recommendations from local agencies. Its management has been running quite well based on the applicable regulations while still prioritizing the discipline and behavior of ASN even though it is not yet optimal.